PENGARUH BIAYA PESTISIDA DAN BIAYA PUPUK TERHADAP PENDAPATAN PETANI DI DESA SERADING KECAMATAN MOYO HILIR - Nining Sudiyarti; K Kurniawansyah; Jihan Faradila (Pusat Riset dan Publikasi, 2022)
This study aims to analyze whether the cost of pesticides and fertilizer costs affect the income of farmers in Serading Village, Moyo Hilir District, Sumbawa Regency. Primary data from 84 samples of rice farmers in Serading Village during one growing season have been analyzed to answer the research objectives. The analytical tool used is Multiple Linear Regression with proposive sampling method. The results of the analysis show that the t-count for the cost of pesticides and fertilizer costs are as follows; (4.887; 0.938) while T table for n = 84 with a confidence level of 5% (? = 0.05) is 1.671 and F-count is 656.010 while F-table 5% (n-k) (k-1) or (0.05; 82.1) is 3.15 meaning Fcount > Ftable so that the null hypothesis is rejected and the alternative hypothesis is accepted, then the two explanatory variables together and significantly affect the variables described. Based on the results of the analysis that the labor cost variable has a significant positive effect up to a 5% confidence level on farmers' income in Serading Village, Moyo Hilir District, while the pesticide cost variable and fertilizer cost have a positive but not significant relationship in influencing farmers' income in Serading Village, Moyo Hilir District.